THE CONSTITUTIONAL DIMENSION OF THE RIGHT TO A HEALTHY ENVIRONMENT - Oana ŞARAMET (Challenges of the Knowledge Society)
Paradoxically, for some of us, and first of all, our lives depend on the Planet Earth on which we live. A healthy Planet Earth will allow us a beautiful, long and healthy life. In international treaties or conventions, as well as in constitutions, there is written about the right to a healthy environment, a right that is usually recongnized to each human being. Although this right is recognized, protected and even guaranteed, shouldn't we speak about ourfundamental duty to ensure a healthy environment? On the other hand, even if we are speaking about the right or the duty to a healthy environment, or both of them, first of all, from a legal point of view, there should be a constitutional regulation and not just the need to ensure a healthy environment. This article, being the first step in analyzing this fundamental right of every person, examines some of the international regulations of the right to a healthy environment, but also some of the provisions from different documents of international organizations at regional level, like Council of Europe, or European Union, or Organization of American States, or African Commission on Human and Peoples' Right, and also from eleven constitutions of Eastern Europe countries, but also some aspects regarding the content of this right.